City Design, Normalization, and Social Life - Fernández Rojas, Elizabeth (2019)
In current times of globalization like those of our competition, the idea of constituting a city from the institution of its design as an essential guiding axis, is a relevant determination both for the gestation of the adapted physical space in question, as well as for the daily development of the humanity; because it is contemplated that insofar as there is an integral constitution governed by the adequate planning of its spatial and temporal components, the urban problems that afflict to big cities will in all probability decrease. In front such distinction, it is important to question: Who is the entity in charge of designing or redesigning the city? State, specialist, society? For us it is evident that the answer to such questions, in a large extent, is implicit in the effectiveness and conducive application of the normative mechanisms that presume to favor the prospective continuity of any adapted physical space, a particular situation that in theory, should facilitate the person the interaction not only with other person, but also in reciprocity, with the physical space that surrounds them in the execution of his daily life and the demands that the social environment demands.